Carinal resection and reconstruction in thoracic malignancies. Issue 3 (29th May 2014) - Shin, Sumin; Park, Joon Suk; Shim, Young Mog; Kim, Ho Joong; Kim, Jhingook
<x xml:space="preserve">Abstract</x> Background and Objectives The purpose of this study was to present clinical outcomes of malignant tumors involving the carina after surgery in order to establish the management guidelines. Methods Between 1996 and 2011, 30 patients underwent carinal resection and reconstruction for malignancy involving carina. We retrospectively analyzed their medical records. There were 22 cases of common type of NSCLC (squamous cell carcinoma/adenocarcinoma/large cell neuroendocrine carcinoma) and eight cases of carcinomas of salivary gland type (adenoid cystic carcinoma/mucoepidermoid carcinoma). Results Seventeen right sleeve pneumonectomies, two left sleeve pneumonectomies, nine carinal sleeve right upper lobectomies, and two airway resections and reconstructions without lung resection were performed. There were no in‐hospital mortalities. Eleven postoperative morbidities occurred including three cases of acute respiratory distress syndrome following pneumonectomy. Late complications occurred in eight patients including three cases of anastomotic stenosis. During follow‐up, 12 mortalities occurred, including 6 cancer‐related mortalities. The 5‐year overall survival rate (OS) and disease‐free survival rate (DFS) were 66.3% and 52.9%, respectively. Conclusions Malignant tumors involving the carina can be controlled with carinal surgery with acceptable mortality and morbidity. Patients with thoracic malignancy involving the carina should be considered as surgical candidate based on disease extent and functional status. J. Surg. Oncol. 2014 110:239–244. © 2014 Wiley Periodicals, Inc.